PENGEMBANGAN STANDAR OPERASIONAL PROSEDUR PADA BIDANG PEMBINAAN PEMERINTAHAN DESA KABUPATEN TAKALAR - Rahman, Aulia; Fadillah Nur, Dwiyanti Dhifara (ADMIT: Jurnal Administrasi Terapan, 2023)
Based on existing regulations, every government organization is required to have service standards, one of which is SOP. One of the benefits of SOP is to improve government performance to make it more effective and efficient. The results of the pre-research interviews found that there were several SOPs at the Takalar District Social Service and PMD, especially in the Village Administration Development Sector that needed to be updated, so the purpose of this study was to develop or update Standard Operating Procedures (SOPs), especially in the Village Administration Development Sector. Community and Village of Takalar Regency. The research method used is a qualitative method with a descriptive research design. Data collection techniques in this study used interviews, observation and document review. While data analysis uses (1) data reduction, (2) data presentation and (3) drawing conclusions. Then to test the validity of the data, this study used a data validity test with source triangulation. The outputs or results of this study are SOPs for Supervision and Assistance in Village Financial and Asset Management, SOPs for Development of Village Financial and Asset Management, SOPs for Verification and Reporting on the Implementation of Village Fund Allocations, and SOPs for Compilation and Development of Village Financial Information Systems.